Corruption’s and Democracy’s Effects on Economic Growth - Zaouali, Amira (International Journal of Business, Economics and Management, 2014)
Economists have a long argue that political process such as democracy and corruption are important for economic growth. Our objective in this paper is to demonstrate that one of democracy’s indirect positive effects is its ability to mitigate the negative effect of corruption on economic growth. Although most democratic countries in our sample have a high level of corruption, the electoral mechanism inhibits leaders from engaging in acts of corruption that cause damage to economic performance and thus jeopardize their political survival. Utilizing a dynamic panel data approach for more than 40 countries over the period 2000- 2011, the results show that in democratic countries, corruption has no significant effect on economic growth, while the non-democratic countries suffer the negative effects of corruption that retard economic growth.